Towards a European small-scale fishing vessel tracking programme: Overview, challenges and opportunities - Tania Mendo; Anna Mujal-Colilles; Einar Hjorleifsson; Pamela Lattanzi; Luca Marsaglia; Mark James; Marta M. Rufino; Helen Holah; Oliver Tully; Jose Rodriguez-Gutierrez; Patrik Jonsson; Estanis Mugerza; et al. (Marine Policy, 2026)

Reflectance spectroscopy (200-4200 nm) of the red-sloped C2 carbonaceous chondrites MET 00432, Tagish Lake, Tarda, and WIS 91600 (“CT” grouplet) - Edward A. Cloutis; Devin L. Schrader; Daniel M. Applin; Tomoki Nakamura; Timothy D. Glotch; Takahiro Hiroi; Moe Matsuoka; Michael E. Zolensky; Joshua P. Emery; Kristi M. Peters (Icarus, 2026)

Early Imaging Biomarkers of Cartilage Strain After ACL Reconstruction Predict Patient Pain and Altered Knee Loading - Emily Y. Miller; Timothy Lowe; Hongtian Zhu; Woowon Lee; Pablo F. Argote; Danielle Dresdner; James Kelly; Rachel M. Frank; Eric McCarty; Jonathan Bravman; Daniel Stokes; Nancy C. Emery; et al. (Annals of Biomedical Engineering, 2026)
Purpose To investigate temporal evolution of cartilage strain and relaxometry following ACL reconstruction, and examine associations between MRI metrics, pain, and knee loading patterns during gait as potential early markers of cartilage degeneration. Methods Twenty-five participants (15 female, 10 male; mean age 25.6 years) undergoing ACL reconstruction completed MRI assessments at 6 and 12 month post-surgery, including displacement-encoding MRI (intratissue strain) and quantitative relaxometry (T2, T2*, T1ρ). Pain was evaluated using patient-reported outcome scores. Gait analysis quantified knee adduction moment, knee extension moment, and knee flexion moment at 12 months in a subset of patients. Correlations between MRI metrics in cartilage contact regions, patient-reported outcomes, and knee loading were evaluated. Results Between 6 and 12 month post-reconstruction, increased tibial compressive and transverse strains correlated with worsening pain, while increased tibial shear strain associated with reduced pain and improved outcomes. Participants demonstrating greater symptom improvement exhibited higher knee adduction moments, which associated with favorable compositional changes including decreased femoral T1ρ and decreased tibial hydrostatic strain. Higher knee extension moments associated with increased tibial compressive and hydrostatic strain. Conclusion Cartilage strain and T1ρ changes associate with pain and altered loading patterns, suggesting potential as early post-traumatic osteoarthritis markers. The observed links between knee loading patterns and cartilage structural changes highlight beneficial adaptation of the reconstructed knee to mechanical loading, and potential avenues for early therapeutic (gait-modifiable) intervention. Advanced MRI may enable early identification of at-risk patients following ACL reconstruction.

The capability of electronic monitoring to measure logbook reporting performance and improve data for scientific analyses - Timothy J. Emery; Rocio Noriega; Mahdi Parsa; Don Bromhead; Trent Timmiss (Fisheries Research, 2025)

Genomic analysis of a parasite invasion: Colonization of the Americas by the blood fluke Schistosoma mansoni - Roy N. Platt; Winka Le Clec'h; Frédéric D. Chevalier; Marina McDew‐White; Philip T. LoVerde; Rafael Ramiro de Assis; Guilherme Oliveira; Safari Kinung'hi; Amadou Garba Djirmay; Michelle L. Steinauer; Anouk Gouvras; Muriel Rabone; et al. (Molecular Ecology, 2022)
Schistosoma mansoni , a snail‐borne, blood fluke that infects humans, was introduced into the Americas from Africa during the Trans‐Atlantic slave trade. As this parasite shows strong specificity to the snail intermediate host, we expected that adaptation to South American Biomphalaria spp. snails would result in population bottlenecks and strong signatures of selection. We scored 475,081 single nucleotide variants in 143 S. mansoni from the Americas (Brazil, Guadeloupe and Puerto Rico) and Africa (Cameroon, Niger, Senegal, Tanzania, and Uganda), and used these data to ask: (i) Was there a population bottleneck during colonization? (ii) Can we identify signatures of selection associated with colonization? (iii) What were the source populations for colonizing parasites? We found a 2.4‐ to 2.9‐fold reduction in diversity and much slower decay in linkage disequilibrium (LD) in parasites from East to West Africa. However, we observed similar nuclear diversity and LD in West Africa and Brazil, suggesting no strong bottlenecks and limited barriers to colonization. We identified five genome regions showing selection in the Americas, compared with three in West Africa and none in East Africa, which we speculate may reflect adaptation during colonization. Finally, we infer that unsampled populations from central African regions between Benin and Angola, with contributions from Niger, are probably the major source(s) for Brazilian S. mansoni . The absence of a bottleneck suggests that this is a rare case of a serendipitous invasion, where S. mansoni parasites were pre‐adapted to the Americas and able to establish with relative ease.

World Octopus Fisheries - Warwick H. H. Sauer; Ian G. Gleadall; Nicola Downey-Breedt; Zöe Doubleday; Graham Gillespie; Manuel Haimovici; Christian M. Ibáñez; Oleg N. Katugin; Stephen Leporati; Marek R. Lipinski; Unai Markaida; Jorge E. Ramos; et al. (Reviews in Fisheries Science & Aquaculture, 2021)

A Robust Métier-Based Approach to Classifying Fishing Practices Within Commercial Fisheries - Mahdi Parsa; Timothy J. Emery; Ashley J. Williams; Simon Nicol (Frontiers in Marine Science, 2020)

The use of electronic monitoring within tuna longline fisheries: implications for international data collection, analysis and reporting - Timothy J. Emery; Rocio Noriega; Ashley J. Williams; James Larcombe; Simon Nicol; Peter Williams; Neville Smith; Graham Pilling; Malo Hosken; Stephen Brouwer; Laura Tremblay-Boyer; Thomas Peatman (Reviews in Fish Biology and Fisheries, 2018)

Does ‘race to fish’ behaviour emerge in an individual transferable quota fishery when the total allowable catch becomes non‐binding? - Timothy J Emery; Klaas Hartmann; Bridget S Green; Caleb Gardner; John Tisdell (Fish and Fisheries, 2014)
Successful individual transferable quota ( ITQ ) management requires a binding (constraining) total allowable catch ( TAC ). A non‐binding TAC may result in a shift back towards open access conditions, where fishers increasingly compete (‘race’) to catch their share of the total harvest. This process was examined by comparing fishing fleet behaviour and profitability in the T asmanian southern rock lobster ( J asus edwardsii ) fishery ( TSRLF ), A ustralia. Between 2008 and 2010, the TSRLF had a non‐binding TAC and effectively reverted to a regulated, limited‐entry fishery. Fishers' uncertainty about future profitability and their ability to take their allocated catch weakened the security characteristic of the ITQ allocation. The low quota lease price contributed to an increase in fleet capacity, while the more limited reduction in quota asset value proved an investment barrier, hindering the autonomous adjustment of quota towards the most efficient fishers. In the TSRLF , catch rates vary more than beach price and are therefore more important for determining daily revenue (i.e., price x catch rate) than market price. Consequently, fishers concentrated effort during times of higher catch rates rather than high market demand. This increased rent dissipation as fishers engaged in competitive race to fish to be the first to exploit the stock and obtain higher catch rates. The history of this fishery emphasizes the need for a constraining TAC in all ITQ fisheries, not only for stock management, but also to manage the security of the ITQ allocation and prevent unanticipated and undesirable changes in fisher behaviour and fishery profitability.